Development of Android Application on Digital Literacy: The Use of Technology Media for High School - Setyoko Setyoko; Ayu Wahyuni; Roni Priyanda (STAI Hubbulwathan Duri, 2023)
Learning materials for Biology were still arranged in the form of hard-copy books in a State High School Langsa. Meanwhile, in the digital era, learning resources must be available in digital form and can easily be accessed on any electronic gadget, such as smartphones. Moreover, digital literacy competence becomes an urgent priority for students to achieve learning goals. This study aims to develop an Android-based application containing the topic of biodiversity based on local potentials. Also, it determines students’ digital literacy in using the platform. This study applied the ADDIE model as the instructional design, which involved 29 first-year high school students. The data were collected through validation sheets of relevant experts and rubrics of digital literacy skills. The data were then analysed by scoring the validation results and statistical Cluster Test. The results show that the validations done by Android and learning material experts (83.33 and 87.55) are strongly valid, with no revision required. The same validation (94.58) is also found by testing the 29 samples. The Cluster Test divided two groups into Group 1, having no technology mastery (5 students) and Group 2, having the capability to use technology (24 students). The significance test on each indicator of digital literacy resulted in a significance value of 0.01, 0.00 and 0.00, which was lower than the degree of freedom of 0.05. Therefore, both groups have different digital literacy skills in the use of technology. The developed android media is limited to the material of cultural biodiversities by integrating local potencies on flora and fauna living in mangrove areas.